Endocan expression is correlated with poor progression-free survival in patients with pancreatic neuroendocrine tumors. Issue 41 (October 2017) - Lin, Liang-Yu; Yeh, Yi-Chen; Chu, Chia-Huei; Won, Justin G.S.; Shyr, Yi-Ming; Chao, Yee; Li, Chung-Pin; Wang, Shin-E; Chen, Ming-Huang
Abstract : Abstract: Endocan expression has been reported to be associated with aggressive tumor progression and poor outcomes in various cancers, such as breast cancer, renal cell cancer, lung cancer, gastric cancer, and pituitary adenomas. However, the prognostic significance of endocan in neuroendocrine tumors remains unknown. Thus, the aim of this study was to determine the correlation between endocan expression in pancreatic neuroendocrine tumor (PNET) tissues and progression-free survival. This study included 73 patients with confirmed PNETs who were treated in a single tertiary center in north Taiwan between 1992 and 2015. Immunohistochemical endocan expression and microvessel density (MVD) were examined, and the relationships between these parameters and other clinicopathological characteristics were analyzed. The abovementioned patients were divided into groups according to their endocan expression levels (≥1% or <1%) and median MVDs. Negative endocan expression ( P  = .002) and a high MVD ( P  < .001) were significant and favorable prognostic factors for progression-free survival. However, positive endocan expression was significantly associated with a low MVD ( P  = .037) and tumor mitosis (Ki-67 index) ( P  = .028). Multivariate Cox regression analysis showed that positive endocan expression (hazard ratio: 4.778, P  = .018) and lymph node involvement (hazard ratio: 5.121, P  = .005) were independent prognostic factors for tumor recurrence. In conclusion, endocan expression was correlated with poor clinical outcomes in PNETs. Our data indicated that endocan expression may be a reliable marker for predicting tumor recurrence in patients with PNETs. Abstract : Supplemental Digital Content is available in the text